Step 1

We have to find the factor of polynomial:

xy+11x−5y−55

Factorization is the process of taking common from various terms and that common terms are known as factor of that expression.

We can see that x is common in xy and 11x

and −5 is common in −5y and −55

since, 55=11 xx 5

Step 2

Finding factor of the polynomial,

xy+11x−5y−55=x(y+11)−5(y+11)

Here y+11 is common,

xy+11x−5y−55=x(y+11)−5(y+11)

=(y+11)(x−5)

Hence, factorization of the given polynomial is (y+11)(x−5) and factors are y+11 and x−5.

We have to find the factor of polynomial:

xy+11x−5y−55

Factorization is the process of taking common from various terms and that common terms are known as factor of that expression.

We can see that x is common in xy and 11x

and −5 is common in −5y and −55

since, 55=11 xx 5

Step 2

Finding factor of the polynomial,

xy+11x−5y−55=x(y+11)−5(y+11)

Here y+11 is common,

xy+11x−5y−55=x(y+11)−5(y+11)

=(y+11)(x−5)

Hence, factorization of the given polynomial is (y+11)(x−5) and factors are y+11 and x−5.